Language Creativity in The Era of Creative Industries: Cognitive Processes of Language - Widada, Dwi Masdi (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The development of the creative industry is a phenomenon of dimension of production. Facing the phenomenon of the creative industry increasingly rapidly, language learning has a strategic position. This position is seen in student competence in language learning. The food product business becomes the foundation for acquiring a language creative label. This affects the quality of the product. This quality impacts the practice of communicating or interacting verbally. There are two competencies that become cognitive processes, namely the mastery of substance content and language mastery. Mastery of substance content in the form of the content of meaning in signs and the relationship between meaning of language signs. Language mastery is the mastery of the system that contains the rules of language use. The rules of language are abstract and do not exist in speech, but in the rules themselves. The role of language in the cognitive process of creativity is related to language functions. These functions include referential functions, imaginative functions, instrumental functions, and transactional functions. These functions have the potential to play a role in the cognitive process of creativity. Language can also be considered brain activity. As a brain activity, there are two approaches, namely the approach through neurology and the approach through technology. In terms of neurology, language sounds and concepts are present in the brain. Approach through technology there are three things that need to be considered, namely construction models, theoretical models, and work models. The role of language in the creative industry displays labels or products that speak creatively. The use of creative language plays a label role in the market in the creative industry. This is inseparable from the factor of language thinking in influencing consumers. Someone's cognitive competence will be influenced by the creative factors of language in introducing products. In line with that there is a process of cognitive cognition so that consumers can understand how to think about the label and the products provided. Food products have become a creative language choice. There are various kinds of language creativity in food products with basic ingredients of chicken. This raises the appeal of consumers about the value of taste when associated with language creativity product labels.